The potential of discovery learning models to empower students' critical thinking skills. (February 2020) - Chusni, Muhammad Minan; Saputro, Sulistyo; Suranto; Rahardjo, Sentot Budi
Abstract: Critical thinking skills have become the competencies of educational goals. This article aims to examine the potential of discovery learning models that are applied in science learning to empower students' critical thinking skills. The method used is qualitative with the main source of literature review about discovery learning models and critical thinking skills. The results of the analysis of the discovery learning model literature with orientation, hypothesis generation, hypothesis testing, conclusion, and regulation stages. Discovery learning model has the potential to empower critical thinking skills starting from the hypothesis generation stage which aims to provide a rational argument from a real phenomenon orientation phase which is continued by the process of interpretation, analyzing, evaluating, concluding the experimental results of the hypothesis testing stage until the right conclusion is obtained from the experimental results.